The matching design of electromagnetic parameters for obtaining excellent microwave-absorption properties by numerical simulation method - Jiang, Linwen; Yang, Shanshan; Wu, Anhua; Liu, Jinjun; Chen, Hongbing (Journal of electromagnetic waves and applications, 2018)
Currently, most of microwave-absorption work has focused on the theoretical formula and design rules of microwave absorber in broadband absorption at low frequencies, especially below 6 GHz. In this work, the detailed matching relation of complex permeability, permittivity, absorber thickness, and microwave-absorption properties were studied by setting up the numerical simulation program of microwave absorption according to the transmission-line theory based on cyclic algorithms. By which, the reason why most materials possess weak microwave-absorption performances below 6 GHz was explained, and the methods how to design desired absorbers utilizing the matching relation were also introduced. The concept presented here is suitable and applicable for a tuned microwave-absorber, which is useful while designing a low frequency absorber.